Day-of-the-week effects in Selected East Asian stock markets - Venus, Khim-Sen Liew; Ricky, Chee-Jiun Chia; Syed Azizi Wafa, Syed Khalid Wafa (Economics Bulletin, 2008)
This study examines the day-of-the-week effects in the Taiwan, Singapore, Hong Kong and South Korea stock markets. Various significant day-of-the-week effects, including the typical negative Monday and positive Friday effects are detected in the stock markets Taiwan, Singapore and Hong Kong. Further analysis shows that only Friday effect in Taiwan is sustainable while all other effects disappeared completely after accounting for equity risks. Besides, this study also finds evidences of risk and return tradeoff as well as asymmetrical market effects.